Sutra Adv. Group Sdn Bhd / Nur Dinah Ardini Mohd Zaid - Mohd Zaid, Nur Dinah Ardini (Faculty of Business and Management, 2023)
My internship journey with full of ups and downs began here at Sutra Adv. Group Sdn. Bhd. located at Pinnacle Petaling Jaya. I was placed under Sales & Marketing Department and appointed as a brand ambassador for their client, Budimas Charitable Foundation. The internship started on the 1st of March 2023 and ended on the 15th of August 2023 (24 weeks). During my internship at Sutra Adv. Group Sdn Bhd, I gained a lot of knowledge about the background of the company. It is crucial for me to understand the company’s background as it provide an overview of the company that I have joined. Besides, I also got to learn on the organizational structure and how this company runs which is through face-to-face marketing where I need to meet and greet people to raise awareness and gain sales for our client. Furthermore, being a part of Sutra Adv. Group Sdn. Bhd. has taught me a lot of skills that could lead to my self-development. It can be seen that my social and communication skills has improved as I had to work in a team most of the time. Not to forget, this internship journey has helped me boost my confidence in every aspect of my life.